2022
DOI: 10.3390/ijerph19159240
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapeutic Scoliosis-Specific Exercise Methodologies Used for Conservative Treatment of Adolescent Idiopathic Scoliosis, and Their Effectiveness: An Extended Literature Review of Current Research and Practice

Abstract: Due to the multifactorial etiology of scoliosis, a comprehensive treatment plan is essential for conservative management. Physiotherapeutic scoliosis-specific exercise (PSSE) methods have lately gained popularity for the conservative treatment of scoliosis. The aim of this study was to analyze the PSSE methodologies used for conservative treatment of adolescent idiopathic scoliosis (AIS), as well as their effectiveness. The study was based on an extended literature search conducted in the PubMed, Google Schola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 60 publications
0
28
0
Order By: Relevance
“…Firstly, spinal muscles mediate stability and counteract scoliosis in the straight spine and small-curve AIS but are scoliogenic in further curve progression (>~20 ° of CA). Specific muscle exercises that seem to reduce the risk of AIS progression are indicative of this role of the spinal muscles [ 52 , 70 , 71 ]. Secondly, in the process of maintaining spinal balance, fatigue and morphological changes can occur.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, spinal muscles mediate stability and counteract scoliosis in the straight spine and small-curve AIS but are scoliogenic in further curve progression (>~20 ° of CA). Specific muscle exercises that seem to reduce the risk of AIS progression are indicative of this role of the spinal muscles [ 52 , 70 , 71 ]. Secondly, in the process of maintaining spinal balance, fatigue and morphological changes can occur.…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of the ATR helps estimate IS progression. Schroth training can signi cantly reduce the ATR [29]. The participants in one study who underwent 10 weeks of Schroth training showed signi cant improvements in Cobb angle, thoracic trunk rotation angle, cosmetic trunk deformity, and SRS-22 [1].…”
Section: Discussionmentioning
confidence: 99%
“…A range of treatments for AIS are available and these range from exercises to bracing and finally surgery for those with severe disease and a large degree of deviation (i.e., Cobb angle) ( Day et al, 2019 ; Kaelin, 2020 ; Dufvenberg et al, 2021 ; Bowden et al, 2022 ; Park et al, 2022 ; Seleviciene et al, 2022 ; Turner et al, 2022 ; Zaina et al, 2022 ). For those patients with severe disease and needing surgery, the implantation of rods and screws can alleviate the curvature-associated complications but can also affect quality of life during post-skeletal maturity.…”
Section: Sex Differences In Risk For Injury To Msk Tissues During Dev...mentioning
confidence: 99%